Effect of stem-bark extract of some common plants on non-target fresh water fish Channa marulius (Ham.) - Singh, D; Singh, A (Indian Journal of Fisheries, 2011)
Stem-bark extracts of four different plants (Euphorbia royleana, Jatropha gossypifolia, Nerium indicum and Thevetia peruviana) caused mortality and biochemical changes in freshwater non-target fish Channa marulius. It was found that dilute stem-bark powder was effective in killing the fishes. The ranking of toxicity of four plants was N. indicum > E. royleana > J. gossypifolia and T. perucviana. Biochemical changes were observed in gonad tissue, after exposure to 40% and 80% of LC50 (24h) of stem-bark extract of all plants. Withdrawal experiments, showed recovery in total protein, total free amino acid, while partial slow recovery observed in glycogen level after 144 h on termination of experiment. It has been suggested that the alterations at both level (metabolic and enzyme) is due to activation of protein kinase C. These extracts show mortality at higher concentration and recovery after 7th day of withdrawal. So, the lower doses of purified form of stem-bark can be used as bio-pesticides for the control of aquatic weeds without environmental hazards.